Systematic discovery of mutation-specific synthetic lethals by mining pan-cancer human primary tumor data - Subarna Sinha (Nature Portfolio, 2017)
There are no robust methods for systematically identifying mutation-specific synthetic lethal (SL) partners in cancer. Here, the authors develop a computational algorithm that uses pan-cancer data to detect mutation-andcancer-specific SL partners and they validate a novel SL interaction between mutant IDH and loss of ACACA in leukaemia.